Integrating Blue and Green Economy Philanthropy into Eco-Pedagogy: A Strategic Framework for Strengthening Village SDGs and K-12 Digital Resilience - Yusuf, Yusuf; Misbah, Hanim (Universitas Nahdlatul Ulama Surabaya, 2026)
The rapid transition toward a sustainable global economy necessitates a fundamental shift in K-12 education, particularly in integrating environmental ethics with digital literacy. This research evaluates how Blue and Green Economy philanthropy can be strategically integrated into eco-pedagogy to strengthen Village SDGs and foster digital resilience among students (Ages 7-18). Utilizing a Systematic Literature Review (SLR) and content analysis of high-impact publications (2020-2025), this study proposes a novel